Crisis to Resilience: Cultivating Effective Internal Communication for Employee Engagement and Organizational Trust - Gautam, Prakash Kumar (Quest Journal of Management and Social Sciences, 2024)
Background: Organisational resilience during crises is vital for organisational sustainability, and internal communication could be instrumental for employees' engagement and organisational trust. Objective: This study explores the effect of internal communication on fostering employee engagement and trust during the COVID-19 pandemic. Methods: The study followed a mixed approach: quali-quanti, with ten interviews and a cross-section survey incorporating 383 bank employees during the second web of the COVID-19 pandemic. The qualitative data was analysed using content analysis to draw the framework and variables of the constructs. The survey contained a 5-point Likert scale, and the data were analysed using structural equation modelling. Results: The study shows that internal communication that is transparent, effective feedback, involving, clear, and consistent enhances the employees' engagement and organisational trust. Conclusion: The study concluded that internal communication becomes a decisive factor for organisational resilience during crises. It significantly strengthens the employees' engagement, which positively mediates the effect of internal communication on organisational trust. Contribution: This study provides practical insights for organisations seeking to enhance communication strategies to promote employee engagement and trust during challenging times. It also contributes to the social exchange theory by demonstrating how the reciprocal exchange of organisational care and employee engagement can bolster organisational trust and resilience. Paper Type: Research Paper Keywords: Internal communication, employee engagement, trust, transparent communication, organisational resilience, clarity and consistency in communication, leadership involvement